MPEG-4-based error resilient coding with closed-loop interaction among peripheral and centralised processing modules - Sacchi, C; Conci, N; Prisciandaro, L; De Natale, F (Electronics letters, 2006)
Proposed is a novel MPEG-4-based video coding, the resilience of which is implemented by exploiting region-of-interest scalability together with a closed-loop interaction between a central processing system, devoted to object detection and tracking, and the video coding embedded at sensor level. Results in terms of processing reliability, achieved in a formal way, prove the usefulness of the proposed approach in the context of scene monitoring applications.